Active currency investing and performance benchmarks - Michael Melvin; Duncan Shand (Center for Economic Studies and ifo Institute (CESifo), 2010)
There are no established benchmarks for evaluating currency investment manager performance. Some analysts have suggested that known investing styles like momentum, purchasing power parity, and carry serve as benchmarks. Challenges for this approach include: there is no market portfolio; there are many alternative generic factor constructions; different constructions of the same factor may have low correlations; the 3 factors may not provide diversification; and there is no buy and hold in the FX market. An evaluation of professional currency managers' returns indicates that they are often generated independently from the generic style factors. Skill in timing is what investors should pay for and some managers demonstrate superior skill in timing the factors. Managers are also skilled at minimizing drawdowns relative to the generic factors. The use of generic style factors may be a worst case scenario instead of returns to which an FX investor may aspire.
Keywords: F31; 330; currency investing; performance benchmarks; carry; momentum; purchasing power parity; Börsenmakler; Devisenhandel; Anlageverhalten; Kapitalertrag; Performance Measurement; Zeit; Kaufkraftparität